Genetic study of the Veddas of Sri Lanka. - Ellepola, S.B (My University, 1985)
Possibility that the Veddas may have had a link with the homosapiens balangodensis (" Balangoda man") and his ancestors who belonged to the paleolithic and mesolithic periods of Sri Lanka in addition to the link with the Sinhalese. One of the interesting features seen in the Veddas when compared with Sinhalese was the higher frequency of haemoglobin E and of glucose six phosphate dehydrogenase deficiency in them. There is also a higher incidence of hepatitis B antigen and antibodies in the Veddas when compared with the Sinhalese. A comparison of the allele systems of the Veddas and Sinhalese show a genetic identity between them of 0.9905 with a genetic distance of 0.0095 and a phylogenetic time of 47,500 years